Perancangan Skema Penyediaan Air Baku Mandiri di Area Gedung Fakultas Teknik Universitas Pancasila Jakarta Selatan - Juniarti, Atie Tri; Soenarto, Bambang; Al Hasyir, Muhammad Humaam (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2025)
In recent years, students and academic staff at the Faculty of Engineering, Universitas Pancasila, South Jakarta, have experienced domestic water shortages due to insufficient water supply. To address this, a rainwater harvesting scheme utilizing AARS (Artificial Aquifer and Rainwater Storage) and NARS (Natural Aquifer and Rainwater Storage) systems is proposed. Calculations indicate the need for 16 standard AARS units, but two alternatives have been designed to reduce costs and optimize available land. Alternative 1 proposes 6 AARS units (9.30 m x 3.33 m x 2.50 m) with maintenance wells measuring 1.50 m in diameter and 7 m in depth, while Alternative 2 consists of 3 units (9.0 m x 5.29 m x 2.50 m) with similar maintenance wells. Both alternatives offer a water production capacity of 4,350 liters/day. Additionally, the remaining 998 m² of roof area will be utilized in a shallow NARS scheme. In a 20 m x 35 m parking lot, 20 NARS units and 2 utilization wells are planned, with excess water discharged into surrounding areas. The combined AARS-NARS system can meet the Faculty’s daily water demand of 6 m³, with AARS supplying 4.35 m³ and NARS covering the remaining 1.65 m³. This system combination has the potential to be a sustainable solution for urban water needs, with its implementation expected to serve as an efficient water management model, especially in urban environments.